(untitled) (Archaeologia Adriatica, 2017)
The author presents the results of five campaigns of submarine archaeological research in Pocukmarak bay on the island of Silba focusing on a stone embankment – quay which functioned as a small waterfront in the bay. Former researchers noticed material evidence from classical antiqity and Late Antiquity in immediate hinterland of the bay. Late antique quay consists of stone sarcophagi incorporated into a stone embankment. In addition to stone finds, wood remains were found in the foundation of the stone embankment. These remains of wooden structures were used as fundament in the segment where the embankment spanned the sand bed. According to 14C analysis the wood used for quay construction was felled in the period between 425 and 595.